Clobazam as an adjunctive therapy in treating seizures associated with Lennox–Gastaut syndrome - Leahy JT (Dove Medical Press, 2011)
Jennifer T Leahy1, Catherine J Chu-Shore1,2, Janet L Fisher3 1Massachusetts General Hospital, Department of Neurology, Programs in Neurophysiology and Epilepsy, Boston, MA, 2Harvard Medical School, Boston, MA, 3University of South Carolina School of Medicine, Department of Pharmacology, Physiology and Neuroscience, Columbia, SC, USA Abstract: Lennox–Gastaut syndrome (LGS) is a devastating childhood epilepsy syndrome characterized by the occurrence of multiple types of seizures and cognitive decline. Most children suffer from frequent seizures that are refractory to current medical management. Recent clinical trials have suggested that addition of clobazam may improve the clinical outcome for some LGS patients. Although clobazam has been available for over five decades, it has only recently been approved by the US Food and Drug Administration for this indication. As a 1,5-benzodiazepine, clobazam is structurally related to the widely used 1,4-benzodiazepines, which include diazepam. Clobazam has been shown to modulate GABAergic neurotransmission by positive allosteric modulation of GABAA receptors, and to increase expression of transporters for both GABA and glutamate. The active metabolite n-desmethylclobazam (norclobazam) also modulates GABAA receptors, and the relative importance of these two compounds in the clinical effectiveness of clobazam remains an open question. Clinical trials involving clobazam as an addon therapy in a variety of pediatric epilepsy populations have found a significant improvement in seizure control. In patients with LGS, clobazam may have greatest efficacy for drop seizures. Longstanding clinical experience suggests that clobazam is a safe and well tolerated antiepileptic drug with infrequent and mild adverse effects. These results suggest that adjunctive treatment with clobazam may be a reasonable option for LGS patients, particularly those who are treatment-resistant. Keywords: benzodiazepine, epilepsy, gamma aminobutyric acid, pediatric, pharmacoresistance